Solution for nonlinear Duffing oscillator using variable order variable stepsize block method - Rasedee, AFN; Sathar, MHA; Ishak, N; Kamarudin, NS; Nazri, MA; Ramli, NA; Irneza Ismail; Sahrim, M (Penerbit UTM Press, 2024)
Indexed by WOS